GREEN HUMAN RESOURCE MANAGEMENT PRACTICES TOWARDS ORGANIZATIONAL COMMITMENT AT PT BAHTERA UTAMA MAGNARINDO SURABAYA - Kurniawati, Masmira; Oktarina, Chentia Aisya (LPPM STIE Muhammadiah Bandung, 2023)
Development impact pollution causes significant health problems and environmental pollution. Each country has different problem impacts depending on the massive position of the industry being run. This article observes that environmental pollution occurs a lot in the development of the latest industry and this is a bad issue for the sustainability of the global economy. This research is a qualitative research that uses in-depth interviews with several key research informants. Data interpretation was obtained from interviews that discussed the relationship between research themes, namely green human resource management. This research approach is descriptive-qualitative so that researchers collect data from interviews, observations and documentation which are then analyzed to form a natural conclusion of the study. The location of this research is PT Bahtera Utama Magnarindo (BUMI) in Surabaya City. The results of this study show that the marketing field of PT Bahtera Utama Magnarindo carries out directions from superiors directly based online, considering that the company's main field is the service sector so that it prioritizes online marketing. This online marketing concept is indirectly an application of green human resource management principles in the marketing field of an organization. Environmental integrity is maintained when the company's performance process takes place and maintains the ecological conditions of the environment around the company.